Dinoflagellate cysts in surface sediments at Van Phong Bay, Khanh Hoa Province, Vietnam: distribution, abundance and potentially harmful algal blooms - Luom, Phan Tan; Hai, Doan Nhu; Lam, Nguyen Ngoc (Academia Journal of Biology, 2021)
Studies on dinoflagellate cysts provide important knowledge on the ecology of dinoflagellates and harmful algal blooms (HABs). In this study, distribution and abundance of dinoflagellate cysts in surface sediments from 17 stations at Van Phong Bay were analyzed. There were 55 different types of cysts representing 3 orders and 18 genera, and 8 unidentified cyst types recorded. Peridiniales was the most diverse order with 29 cyst types, including 20 Protoperidinium cyst types. There were 10 cyst types of 7 potential toxic dinoflagellate species and 4 of bloom forming species found, indicating a potential risk of harmful algal blooms in Van Phong Bay. Number of cyst types and density ranged from 12 to 31 types and from 115 to 3,760 per gram of dry weight sediment, respectively. Cysts of Leonella granifera were dominant at stations in the mouth of the Bay, while Scrippsiella trochoidea cysts dominated at all stations. Shannon diversity index (H’) was low, varying from 1.192.72. There were two distinct cyst assemblages identified with 40% Bray-Curtis similarity, assemblage I with 2 stations (VP09 and VP10), and assemblage II with the other stations.